Effects of compression stockings on ankle muscle H‐reflexes during standing. Issue 4 (10th November 2016) - Espeit, Loic; Pavailler, Sebastien; Lapole, Thomas
ABSTRACT: Introduction: Wearing compression stockings (CS) may improve postural stability through additional cutaneous feedback. The aim of this study was to further determine how wearing CS could influence spinal excitability by investigating ankle muscle H‐reflexes. Methods: Fifteen subjects were asked to stand barefoot on a rigid floor with their eyes open. H‐reflex amplitude was measured in the soleus (SOL), fibularis longus (FL), and tibialis anterior (TA) muscles, with and without CS. Concomitant M‐waves and baseline electromyographic activity (EMG) were monitored. Results: Baseline EMG activity and concomitant M‐wave amplitude remained stable across conditions in all tested muscles. Although CS did not affect the H‐reflex in the SOL (+0.8 ± 19.2%; P = 0.77) and FL (–10.0± 33.2%; P = 0.28) muscles, the TA H‐reflex was significantly depressed (–21.9% ± 24.0%; P = 0.03). Conclusions: These results suggest decreased spinal motoneuron excitability and/or increased presynaptic inhibition of Ia‐afferent terminals through increased cutaneous inputs provided by CS while standing. Muscle Nerve 55 : 596–598, 2017